2021
DOI: 10.1155/2021/5598818
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Effects of Cicadae Periostracum on Mice and Its Antiapoptotic Effects in H2O2‐Stimulated PC12 Cells via Regulation of PI3K/Akt/Nrf2 Signaling Pathways

Abstract: Cicadae Periostracum (CPM), a commonly used animal traditional Chinese medicine (TCM), possesses antifebrile, spasmolytic, antiasthmatic, and antiphlogistic effects. In our present paper, we aimed to systemically investigate the antiepileptic effects of CPM in epileptic mice and explore the related molecular mechanism. Pentylenetetrazole- (PTZ) and strychnine-induced convulsion mice were established, and the results showed CPM could prolong the latency of convulsion and death and improve the neuronal damage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Subsequently, Cyt-C in the cytoplasm activates caspase-9, which in turn activates Caspase-3. As the ultimate executor of apoptosis, caspase-3 activation triggers the occurrence of apoptosis ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Cyt-C in the cytoplasm activates caspase-9, which in turn activates Caspase-3. As the ultimate executor of apoptosis, caspase-3 activation triggers the occurrence of apoptosis ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, H 2 O 2 is a small molecule compound with high cell membrane permeability. At the same time, as an important member of the ROS family, H 2 O 2 can also generate hydroxyl radicals, which in turn cause oxidative stress and even cell death ( Zhang et al, 2021 ). Therefore, PC12 cells stimulated by H 2 O 2 are often used in drug screening models for various neurodegenerative diseases, and this model was also selected as a cell model to verify the anti-AD effect of AOF in this experiment ( Bie et al, 2021 ; Vahdati et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JC-1 was commonly considered a perfect probe for assessing ΔΨm. In addition, apoptosis rate was measure by flow cytometry analysis ( Zhang et al, 2021a ). Our results revealed that treatment with HEO remarkably decrease apoptosis in CORT-injured PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to identify more safe and effective drugs for MI. With a long history of clinic use, Traditional Chinese medicine (TCM) has great advantages to treat cardiovascular diseases ( Duan et al, 2021 ; Zhang et al, 2021a ), which can be seen as a resource library for alternative drugs of MI ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%